A new species of the genus Philothermus Aubé (Coleoptera: Cerylonidae) from Great Smoky Mountains National Park, U.S.A. - Gimmel, Matthew L.; Slipinski, Adam (Zootaxa, 2007)
A new species of cerylonid with reduced eyes from the Great Smoky Mountains, Philothermus stephani sp. n., is described and illustrated. A revised key to the North American species of Philothermus is presented.